2014
DOI: 10.1038/ismej.2014.179
|View full text |Cite
|
Sign up to set email alerts
|

Diet is a major factor governing the fecal butyrate-producing community structure across Mammalia, Aves and Reptilia

Abstract: Butyrate-producing bacteria have an important role in maintaining host health. They are well studied in human and medically associated animal models; however, much less is known for other Vertebrata. We investigated the butyrate-producing community in hindgut-fermenting Mammalia (n ¼ 38), Aves (n ¼ 8) and Reptilia (n ¼ 8) using a gene-targeted pyrosequencing approach of the terminal genes of the main butyrate-synthesis pathways, namely butyryl-CoA:acetate CoA-transferase (but) and butyrate kinase (buk). Most a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 37 publications
13
94
0
Order By: Relevance
“…Further emphasizing the need to more fully characterize this family, and in agreement with previous gene-targeted studies (17,37), we detected many OTUs with low identity to both confirmed sequences and cultured organisms. This work reveals many gaps in our knowledge of the but gene family.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Further emphasizing the need to more fully characterize this family, and in agreement with previous gene-targeted studies (17,37), we detected many OTUs with low identity to both confirmed sequences and cultured organisms. This work reveals many gaps in our knowledge of the but gene family.…”
Section: Discussionsupporting
confidence: 69%
“…Butyrate is centrally important to colonic homeostasis and is present in every vertebrate gut system studied to date (37). The butyrate-producing microbiota has been implicated in host health in many different disease models (35,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47), resulting in increased interest in studying this community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main human colonic butyrate producers belong to two groups of Gram-positive firmicutes: Faecalibacterium prausnitzii in the Clostridium leptum (or clostridial cluster IV) cluster, and Eubacterium rectale/Roseburia spp. in the Blautia coccoides (formerly Clostridium coccoides, clostridial cluster XIVa) (12-15), whereas there are other butyrate-producing groups that have been detected in humans (16)(17)(18).Vegetables belonging to the Brassica genus (Brassicaceae family) contain a number of nutrients with health-promoting properties, such as anticancer actions (19) and effects on cholesterol metabolism (20). These vegetables (Brassica oleracea L. [kale, cabbage, and broccoli], and Brassica rapa L. [turnip]) are unique in that they are rich sources of fiber, carotenoids, and foliate, as well as polyphenols and sulfur-containing compounds (21).…”
mentioning
confidence: 99%